Vitamin D Profile and Disease Activity of JIA During Pandemic Covid-19: Vitamin D Profile and Disease Activity of JIA - Desy Wulandari; Wisnu Barlianto; Tita Luthfia Sari (Journal of Tropical Life Science, 2022)
Vitamin D (25-Hydroxyvitamin D3 [25(OH)D3]) has an important role in the immune system. This study aimed to assess the relationship between 25-Hydroxyvitamin D3 and disease activity in Indonesian children with Juvenile Idiopathic Arthritis (JIA) during pandemic Covid-19. A 12-week randomized control trial was undertaken at Saiful Anwar Hospital between June and September 2021. JIA patients are divided into two groups. The control group (CG), without supplementation, and the treatment group (TG) got a high dose of oral cholecalciferol 2000 IU/day. Serum levels of 25(OH)D3 were measured using an enzyme-linked immunosorbent assay (ELISA). Comparison between serum 25(OH)D3 levels and JIA subtypes, peripheral blood Creactive protein (CRP), erythrocyte sedimentation rate (ESR), and Juvenile Arthritis Disease Activity Score (JADAS-27 Score) were analyzed using SPSS. There was a significant increase in serum 25(OH)D3 levels in treatment group (mean: 27.38 ± 6.39 ng/ml vs 42.26 ± 10.95 ng/ml; P=0.000). The JADAS-27 score significantly decrease in treatment group (14.60 ± 4.04 vs 6.24 ± 1.96; p= 0.000). Serum 25(OH)D3 showed a significant correlation with the JADAS-27 score. The levels of 25(OH)D3 are significantly decreased in children with JIA. Decreased 25(OH)D3 levels may be associated with the etiopathogenesis of JIA. Vitamin D levels have correlations with disease activity. Adjunctive treatment of cholecalciferol improves the disease activity in JIA patients. Keywords: Disease activity, JIA, Pandemic Covid-19, Vitamin D